Variables influencing the in vitro measurement of spontaneous aggregation of human platelets - Claudia Ghali; Antonella Fioretti; Mariangela Scavone; Elena Bossi; Bianca Clerici; Simone Birocchi; Evgeny Popov; Marco Centola; Gianmarco Podda; Marco Cattaneo (Haematologica)
Not available.